2010
DOI: 10.1007/s12117-010-9095-8
|View full text |Cite
|
Sign up to set email alerts
|

Gangs as contractors: the social organization of American Taiwanese youth gangs in Southern California

Abstract: This paper examines the organizational structure and operations of Taiwanese organized crime and youth gangs in Southern California. In-depth interviews were used as the principle method of research. In contrast to transnational criminal conspiracy claims and the La Cosa Nostra model of vertically integrated organizations, our findings suggest that these criminal groups consist of discrete local Taiwanese youth gangs which operate as largely independent economic units that show no substantive and operational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Asian gangsters and the American television family Jeffersons have much in common: they are all trying to "move on up" to acquire a "piece of the pie." This theme permeates across the gangster films from the respective three countries, and reinforces existing scholarship on why individuals join gangs (e.g., Pih et al, 2010). Moreover, upward striving suffuses the relationships of low-level gangsters to middle-level gangsters (dai-los, hyoung-nims, and oyabuns), and the preceding two to the chieftains of a crime group.…”
Section: Eking Out a Living: The Cannibalistic Path Of Upward Strivingsupporting
confidence: 65%
See 1 more Smart Citation
“…Asian gangsters and the American television family Jeffersons have much in common: they are all trying to "move on up" to acquire a "piece of the pie." This theme permeates across the gangster films from the respective three countries, and reinforces existing scholarship on why individuals join gangs (e.g., Pih et al, 2010). Moreover, upward striving suffuses the relationships of low-level gangsters to middle-level gangsters (dai-los, hyoung-nims, and oyabuns), and the preceding two to the chieftains of a crime group.…”
Section: Eking Out a Living: The Cannibalistic Path Of Upward Strivingsupporting
confidence: 65%
“…Furthermore, their participation has led to a reconfiguration of ideology and identities within gangs, as members become entrenched in the logic and ethos of capitalism (Sassen, 2007). In fact, Pih et al (2010) found that the very essence of Asian gangs has undergone a dramatic transformation, with branches of Asian organized crime groups beginning to refer to themselves as "the company." That is to say, gangs as a whole have transitioned from a loosely organized playgroup turned criminal network to economic machines, the difference between legitimate enterprises and criminal ones being the level of coercion and illegal methods employed to achieve their financial objectives (Pih et al, 2010).…”
Section: Economic Benefits Of Gang Membershipmentioning
confidence: 99%
“…With few other job options, community members come to regard the gang as the employer of choice. The gang becomes primarily a business enterprise, an economic entity, rather than a social group [37,43,80,85,96,116].…”
Section: Signs Of Gang Evolutionmentioning
confidence: 99%
“…In gangs in other places around the world, different types of formal structures can be found, including militarized structures in Rio's drug factions and networks of 'franchisees' in Cape Town [46]. In Southern California, Taiwanese gangs each have a clear hierarchical form but operate collectively in "business-like networks" [85].…”
Section: Signs Of Gang Evolutionmentioning
confidence: 99%
“…The bureaucratic model is a rationalized, hierarchical system which is impersonal and rigid in form (Abadinsky 2007). Criminal organisations like the Italian Mafia are "tightly structured in a hierarchical manner, resembling the bureaucracy found in the legitimate economy" (Pih, Hirose and Mao 2010). Various definitions of the bureaucratic model suggest that its characteristics include: a single leader, defined hierarchy, extensive division of labour, rigid and impersonal, various subordinates and code of conduct.…”
Section: Criminal Networkmentioning
confidence: 99%